IMPLEMENTASI PROGRAM LAYANAN TERAPUNG KEAGAMAAN (LANTERA) PADA KANTOR KEMENTERIAN AGAMA KABUPATEN LINGGA KEPULAUAN RIAU - Nurhadiyanti Nurhadiyanti; Agus Saputra; Rika Apriati Ningsih; Firman Abriansya (Jurnal Caraka Prabu, 2026)
This paper discusses the Implementation of the LANTERA Program in Improving Public Services at the Ministry of Religious Affairs Office in Lingga Regency. The LANTERA program is a strategic initiative designed to improve service quality, accelerate administrative service processes, and increase public satisfaction in obtaining religious and administrative services. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies on the implementation of the LANTERA program. In general, the results of this study indicate that the implementation of the LANTERA program in Lingga Regency has been running well and has brought a number of significant improvements in public services. These include increasing the speed of the service process, reducing bureaucratic obstacles, and increasing the transparency of service information to the public. This program has also succeeded in creating a more integrated and systematic service mechanism through the use of information technology, thereby improving the quality of interactions between service officers and the public.